Study on the Civics Programme and Curriculum Civics and Co-coordination for Human Development - Hu, Yanfang (Journal of Theory and Practice of Contemporary Education, 2023)
The proposal and practice of the collaborative nurturing model of curriculum Civics and Civics courses not only enriches the content of ideological and political education, but also innovates the channels of ideological and political education. Exploring the collaborative nurturing model of curriculum Civics and Civics courses in applied colleges and universities is conducive to enhancing the effectiveness of the work of ideological and political education in colleges and universities in the new era, and cultivating newcomers of the era of socialism with Chinese characteristics in the new era for the Party and the country.